Managerial thinking, a study of public managers from developing countries - Rahman, Syedur; Norling, Frederick
This paper focuses on examining the attitudes of public managers towards their own orgnisations. It analyses the responses of 110 public sector managers from 58 different countries of the world while they were in residence for professional development at 12 major universities in the United States. Examining public managers outside their own working environment makes this research on public sector managers to some extent unusual. For purposes of data collection a stratified sample was utilized. The principal instrument consisted of 79 items. Managers were asked to state their attitudes towards problem-solving and decision-making, leadership, job challenge, change, and organizational culture. Primarily de
Keywords: Public Administration; Management; Motivation; Leadership; Government Enterprise; Developing Country; Decision Making; `aGovernment Enterprise-Personnel